Evaluation of Delayed Effective Discharge for Non-Medical Reasons in Patients Admitted to Acute Care Hospitals in Spain: A Scoping Review - Noelia López Luis; Cristobalina Rodríguez-Álvarez; Leticia Cuéllar-Pompa; Ángeles Arias (MDPI AG, 2023)
Delayed discharge for non-clinical reasons is defined as a period of stay that continues after a patient has been deemed medically fit to leave the hospital but is unable to do so for non-medical reasons. This circumstance overburdens the healthcare system and constitutes a major problem for healthcare systems and the patients themselves in this situation. The aim of this study was to evaluate the delay in effective discharge for non-medical reasons for patients admitted to acute care hospitals in Spain. A scoping review followed the Joanna Briggs Institute methodology guidelines to search for and synthesize studies published between 2019 and 2022. To identify potentially relevant documents, the following bibliographic databases were searched: EMBASE, CINAHL and MEDLINE. For the search, we used free terms («delayed discharges», «discharge delays», «bed-blocking», «timely discharge», «unnecessary days» and «inappropriate stays»). Quantitative or qualitative studies published in scientific journals on delayed effective discharge for non-medical reasons for patients admitted to a hospital for any health issue of medical or surgical origin were selected. Information collection of the documents was performed using a structured datasheet specifically developed by the authors. The initial search strategy identified a total of 124 references, which were successively screened to a final selection of 13 studies. To conclude, delayed discharge from a hospital for non-clinical reasons is a multifactorial problem. This may be due to factors internal or external to the hospital, as well as personal factors. The main causes of the delay were similar among the studies found, as were the clinical characteristics of the patients, most of whom were elderly, frail and more dependent due to declining functional capacities. Further studies addressing the socio-familial characteristics of the patients and the perspective of the patient and families would be necessary.